2021
DOI: 10.3389/fspor.2021.692601
|View full text |Cite
|
Sign up to set email alerts
|

Good Food, Good Mood: Perspectives on the Relationship Between Nutrition and Mental Health With Division I Collegiate Athletic Programs

Abstract: Research has shown a strong relationship between nutrition and mental health. Packed schedules and little rest time may make student-athletes more susceptible to mental health issues than the general population, but few athletes are fully aware of the effects that nutrition can have on their mental health. While collegiate athletic programs are beginning to recognize the individual contributions of nutrition and mental health to performance and are hiring sport dietitians and psychologists for their athletes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In addition, balancing eating habits related to the consumption of certain foods can also be an integral part of prevention against negative health consequences of eating disorders and recovery from depression and disordered eating (Jeffrey & Heruc, 2020). To date, various research has confirmed a strong relationship between nutrition status and mental health outcomes among athletes (McCabe et al, 2021). Therefore, the main aim of this exploratory review is to outline the common mental health conditions caused by sports discipline, with a primary focus on depression and disordered eating.…”
Section: Journal Of Coaching and Sports Science | 61mentioning
confidence: 99%
“…In addition, balancing eating habits related to the consumption of certain foods can also be an integral part of prevention against negative health consequences of eating disorders and recovery from depression and disordered eating (Jeffrey & Heruc, 2020). To date, various research has confirmed a strong relationship between nutrition status and mental health outcomes among athletes (McCabe et al, 2021). Therefore, the main aim of this exploratory review is to outline the common mental health conditions caused by sports discipline, with a primary focus on depression and disordered eating.…”
Section: Journal Of Coaching and Sports Science | 61mentioning
confidence: 99%